COST PLAN ANALYSIS UPPER STRUCTURE WORKS - Winda Delfi Lukmana; Ayu Herzanita (Jurnal Infrastruktur, 2021)
The construction of apartment buildings is vulnerable to the occurrence of changes to the cost of the plan that had been budgeted. Including the project of Urban Homes Residential Tower B North Lippo Village which needs to calculate the cost plan from the design stage, to reduce the impact on the implementation phase. This study aims to determine the factors that affect the calculation of cost plan, to know the calculation volume of works, preparation of analysis and cost plans, and to analyze the difference between the cost plan and cost contract. The scope of work for the analysis of the calculation of upper structure in Urban Homes Residential project for the tower B (Urban Two) which starts from the 1st floor to the 42nd floor is to calculate the quantity of the upper structure (shear wall, slab, beam, column, ramp, and parapet wall works), to prepare cost plan using Analisa Harga Satuan Pekerjaan (AHSP) refer to PM-PUPR-28/2016 with the unit rate of wages, materials, and equipment of DKI Jakarta 2021 as well as the cost plan. Cost plan is influenced by location, type of structure and soil conditions, building design and space composition, building size, contract period, and implementation method. The cost required to carry out the upper structure works on this project is Rp. 129,195,120,664 with an area of 89,054.11 m² and the cost per m2 of upper structure works is Rp. 1,523,000.00. The comparison of the cost plan and cost contract is Rp. 3,084,359,691 with a comparison percentage of 2.45% of the cost contract.